Pengaruh Akurasi Berita pada Akun Instagram Detikcom terhadap Kepercayaan Mahasiswa S1 Jurnalistik Universitas Bengkulu - Jannah, Raudhatul; Perdana, Dionni Ditya (TSAQOFAH, 2026)
The development of social media has made Instagram one of the main spaces for disseminating digital news, including through the Detikcom Instagram account. This study aims to analyze the effect of news accuracy on the Detikcom Instagram account on the trust of undergraduate Journalism students at the University of Bengkulu. This study used a quantitative approach with a survey design. The research respondents consisted of 23 students selected through purposive sampling based on the criteria of being active undergraduate Journalism students at the University of Bengkulu, having an Instagram account, and having accessed news from the Detikcom Instagram account. Data were collected using a Likert-scale questionnaire consisting of 15 statement items. Data were analyzed through validity testing, reliability testing, inter-item correlation, and descriptive analysis. The results show that all items had Corrected Item-Total Correlation values above 0.300, ranging from 0.325 to 0.762. The Cronbach’s Alpha if Item Deleted values ranged from 0.874 to 0.893, indicating that the research instrument was reliable. This finding confirms that news accuracy is an important aspect in building students’ trust in digital media. This study contributes to the development of digital journalism studies, particularly regarding the relationship between information quality and young audiences’ trust in news on social media. The implications of this study open opportunities for further research with a more comprehensive analytical model to examine the effect of news accuracy on digital media users’ trust.